Fracture properties of Sn-37Pb and Sn-3.5Ag solder joints - Siow, Kim Shyong. (2008)
Surface mount technology has increasingly become the industry norm and slowly replaced the pin through hole technique. This preference has led to a demand for higher quality solder joints. Besides the traditional role as an electrical connection, the joint needs to be able to act as a load bearing element. The solder must be able to sustain the load during manufacture, transport and use. The most common solder used in the industry is the Sn - Pb family of alloys. In recent years, lead has been linked to many health problems and may be phased out in the future. Intensive studies are being conducted to find suitable replacements for lead-based solders and Sn-3.5Ag is one such solder.